RETRACTED: Intolerance of Uncertainty Scale-12: Psychometric Properties of This Construct Among Iranian Undergraduate Students - Vadivel, Balachandran; Azadfar, Zahra; Talib, Mansor Abu; Mutlak, Dhameer A.; Suksatan, Wanich; Abbood, Abbas Abd Ali; Sultan, Mohammed Q.; Allen, Kelly A.; Patra, Indrajit; Hammid, Ali Thaeer; Abdollahi, Abbas; Chupradit, Supat (Frontiers in Psychology, 2022)
Background: Uncertainty intolerance (IU), the tendency to think or react negatively towards uncertain events may have implication on individuals’ mental health and psychological wellbeing. The Intolerance of Uncertainty Scale-12 (IUS-12; Carleton et al., 2017) is commonly used across the globe to measure IU, however its’ psychometric properties are yet to be evaluated in Iran with a Persian-speaking population. Therefore, the purpose of this research was to translate and validate the IUS-12 among Iranian undergraduate students. Methods: A sample of 410 Iranian undergraduate students (260 females) from the Azad University completed the IUS-12, the Depression Anxiety Stress Scale-2, and the Penn State Worry Questionnaire. Results: The impact score of the translated IUS-12 indicated acceptable face validity. The Content Validity Index (CVI) and the Content Validity Ratio (CVR) indicated the items had acceptable content validity and were deemed essential to the measure. A Confirmatory Factor Analysis (CFA) indicated the scale was composed of the two subscales found in the English-version of the scale (prospective anxiety and inhibitory anxiety), and no items were removed from the scale. Conclusions: The findings support the psychometric properties of the Persian version of the IUS-12. This scale could be used to reliably and accurately measure uncertainty intolerance among adult populations in Iran.